Foraging Activity and Potential Forage Plant Resources Surrounding the Nests of Tetragonula laeviceps - Ni Kadek Deladarmi Yanti; I Made Budiarsa; Manap Trianto; Fatmah Dhafir; Yulia Windarsih; Mursito S Bialangi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
Stingless bees are highly social insects that live in well-organized colonies characterized by a clear division of labor among individuals, including workers, queens, and males. These bees play an important ecological role as pollinators in both natural and agricultural ecosystems. One of the most commonly encountered stingless bee species in Indonesia is Tetragonula laeviceps, which is widely distributed and well adapted to various environmental conditions. T. laeviceps relies on flight activity to forage for nectar and pollen from flowering plants located around its nest. Plants that produce nectar, pollen, and resin, which are further processed into honey and propolis, serve as essential food and material resources for sustaining stingless bee colonies. This study aimed to examine the foraging activity patterns of T. laeviceps and to identify potential forage plant resources surrounding its nest. The research employed a descriptive exploratory design using both qualitative and quantitative approaches. Observations were conducted to record the daily flight activity of bees leaving the nest, returning with pollen, and returning without pollen, as well as to identify plant species that potentially serve as forage sources. The results showed that peak foraging activity occurred between 08:00 and 09:00 WITA, indicated by a high number of bees exiting the nest and returning with or without pollen. Foraging activity gradually declined toward the late afternoon, particularly between 16:00 and 17:00 WITA. This pattern reflects the daily rhythm of stingless bees, which includes an orientation and exploration phase in the morning, an exploitation phase during midday, and a gradual cessation of activity in the late afternoon. Observations of forage resources around the nests of T. laeviceps recorded a total of 13 plant species. Among these, seven species produced both nectar and pollen, three species produced only nectar, and three species produced only pollen. The diversity of forage plants indicates that the environment surrounding the nest provides sufficient and sustainable nutritional resources to support the growth and stability of the T. laeviceps colony.